Variation Symptoms and Resistance Response of Different Types on Orchids (Orchidaceae) Against Odontoglossum ringspot virus (ORSV) Infection - Mahfut Mahfut; Budi Setiadi Daryono (Universitas Lampung, 2019)
Odontoglossum ringspot virus (ORSV) is one of the viruses that are reported to infect the most orchids in Indonesia. Viral infections cause economic losses. This research was conducted to study the introduction of symptoms of infection that appear as the initial stages of disease control. The source of the virus is orchid leaves Phalaenopsis amabilis positively infected by ORSV collected from Magelang. Virus isolation was carried out by mechanical inoculation to indicator plants (Chenopodium amaranticolor and Nicotiana tabaccum). Furthermore, the results of inoculation were multiplied using various types of orchids (Dendrobium, Cymbidium, Chattleya, Phalaenopsis, Spatthoglotis, Liparis, and Pecteilis). Virus detection on orchid tissue was done trough the DAS-ELISA and observation of virus structure using TEM. The results showed that Pectelis sussanae (L.) Raf. was the only orchid plant that was immune against ORSV approached. Dendrobium sp., Cymbidium sp., Chattleya sp., Phalaenopsis sp., and Spathoglotis sp. showed a response of susceptible of ORSV severe infection symptoms, while Liparis sp. were resistant. The variation of resistance from several orchid plant against infection ORSV showed severe symptoms with the incubation periode was seen earlier. The observation of virus structure using TEM showed rigid road shape particle, 300 x 18 nm in size, which is general characteristic of Tobamovirus. This indicate an infection of ORSV is a dangerous disease and require serious control